(untitled) (Tzintzun, Revista de Estudios Históricos, 2022)
This article examines the emergence and consolidation at the national and regional levels of Guatemalan general Carlos Arana Osorio. The article focuses on four elements: its political emergence, its contribution in building alliances with other Central American presidents, its support to them in times of crisis under the silent eye of the Nixon/Kissinger duo, and its role in confronting different domestic institutional areas to achieve the continuity of his political project. It seeks to bring to light elements and temporalities usually overlooked in Central American historiography. Specifically, it seeks to discuss the political violence in Guatemala and the Central American nuances within the Latin American Cold War. This in order to nuance the classical canon that emphasizes violence and US interventionism as axis of politics in the country.